HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN HASIL LOMPAT TINGGI GAYA STRADDLE SISWA PUTRA KELAS V SDN 005 KIAP JAYA KEC. BANDAR SEI KIJANG KAB. PELALAWAN - Sari Nst, Fenny Wulan; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s, the ability of the student’s high jump was not optimal. Researcher found the quality of learning outcomes of sport education still low. This is seen when researchers help making procces patice exam scores high jump with straddle style. Evident from learning outcomes still below average or below standars that class rise to minimal completeness criteria. The purpose of this research is to see how much the correlation of explosive power leg muscle with the result of high jump with straddle style of male student in grade V of 005 Kiap Jaya Primary school of Bandar Sei Kijang District of Pelalawan. Population in this research were all mal student in grade V of 005 Kiap Jaya Primary school who were 28 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 28 people. Research instrument is measurement of explosive power leg muscles used vertical jump test and high jump stradlle style test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there is no correlation explosive power leg muscles with the result of high jump with stradlle style, which shows rhitung(0,177) < rtab (0,381).Key word : explosive power leg muscles, high jump.